Equilibrium Studies on Some Ternary Complexes of Cu(II) with 1,3-Diamino Propane as Primary Ligand and O-O Donor Atoms as Secondary Ligands and its Comparison with Binary Complexes - Sharma, Sangita; N. Patel, Jayshree; Vora, J.J.; Joshi, J.D. (Asian Journal of Chemistry, 2010)
The formation constants of the mixed ligand complexes (CuAL) at 1 : 1 : 1 optimum molar concentration of metal as Cu(II); primary ligand, A = 1,3-diamino propane (1,3-DiaP) and O-O donor atoms as secondary ligand, L = salicylic acid, DL-malic acid, DL-mandelic acid, DL-lactic acid have been determined by modified form of Irving-Rossotti titration technique in aqueous media at constant ionic strength μ = 0.2 M dm–3 at 30 ± 0.1ºC. The difference between the stability of ternary complexes and the corresponding binary complexes has been expressed in terms of parameter Δlog KT. The stabilities of the ternary complexes are explained in terms of π-basicities, structures of secondary ligand and ring size of chelate. Δlog KT values are negative which suggests favourable formation of ternary complexes. The variations of Δlog KT have been explained in terms of M → L π-interaction, size of the chelate ring and steric factors.